2007
DOI: 10.1101/lm.348307
|View full text |Cite
|
Sign up to set email alerts
|

Eye-blink conditioning is associated with changes in synaptic ultrastructure in the rabbit interpositus nuclei

Abstract: Eye-blink conditioning involves the pairing of a conditioned stimulus (usually a tone) to an unconditioned stimulus (air puff), and it is well established that an intact cerebellum and interpositus nucleus, in particular, are required for this form of classical conditioning. Changes in synaptic number or structure have long been proposed as a mechanism that may underlie learning and memory, but localizing these changes has been difficult. Thus, the current experiment took advantage of the large amount of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…It is consistent with the findings of the previous studies using peripheral CS in eyeblink conditioning that cerebellar interpositus nucleus plays an essential role in CR expression [4,27,29,31,66,70,71] . Steinmetz [72] speculated that the cerebellum may only be involved in simple, discrete, aversive, and somatic associative learning that occurs with a relatively short interstimulus interval.…”
Section: Discussionsupporting
confidence: 82%
“…It is consistent with the findings of the previous studies using peripheral CS in eyeblink conditioning that cerebellar interpositus nucleus plays an essential role in CR expression [4,27,29,31,66,70,71] . Steinmetz [72] speculated that the cerebellum may only be involved in simple, discrete, aversive, and somatic associative learning that occurs with a relatively short interstimulus interval.…”
Section: Discussionsupporting
confidence: 82%
“…The air puff signal (US) is relayed by climbing fibers from the medial part of the dorsal accessory inferior olive and/or dorsomedial group of the principal olive to PCs in the C3 or D0 zones of the cerebellar cortex (Mostofi et al, 2010). These olivary parts also give rise to collaterals to the lateral part of the AIN and DLH, respectively (Ruigrok and Voogd, 2000;Pijpers et al, 2005;Sugihara and Shinoda, 2007). Moreover, these CN regions have been shown to influence those parts of the facial nucleus that control the eyelid muscles (Morcuende et al, 2002;Gonzalez-Joekes and Schreurs, 2012).…”
Section: Cs and Us Pathway And Bilateral Contribution Of The Cn To Eymentioning
confidence: 99%
“…Repeated pairings of tone and air puff gradually lead to the development of a timed eyelid closure in response to the tone, which is called the conditioned response (CR). The US is relayed by climbing fibers from specific parts of the inferior olive to Purkinje cells (PCs) in distinctive eyeblink controlling zones of the cerebellar cortex (Hesslow, 1994;Mostofi et al, 2010) and, by way of climbing fiber collaterals, to the lateral part of the anterior interposed nucleus (AIN) of the cerebellar nuclei (CN), including its dorsolateral hump (DLH) (Ruigrok and Voogd, 2000;Pijpers et al, 2005;Sugihara and Shinoda, 2007). The CS is relayed to the same PC zones by mossy fibers originating from the lateral part of the basilar pontine nuclei (BPN) (Kandler and Herbert 1991;Leergaard and Bjaalie, 2007;Halverson and Freeman, 2010;Mostofi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of experimental data demonstrate that, in addition to its major functional role in the regulation of fine motor control, the cerebellum is crucially involved in other important functions such as sensory-motor learning and memory, e.g., conditioned eye-blink responses (20)(21)(22).…”
mentioning
confidence: 99%
“…Recently, it has been shown that the time window for multiple input coincidence detection by hippocampal neurons is unchanged after in vitro LTP only when both excitatory and inhibitory synapses are potentiated (19). Thus, the temporal fidelity for spike generation within a neuronal network requires adequate levels of excitation and inhibition to be maintained.Several lines of experimental data demonstrate that, in addition to its major functional role in the regulation of fine motor control, the cerebellum is crucially involved in other important functions such as sensory-motor learning and memory, e.g., conditioned eye-blink responses (20)(21)(22).Recent studies have shown that the cerebellum also is involved in fear-related memory (23, 24), and it is activated by a sensory stimulus predicting a painful stimulation after conditioning (25,26). In addition, in the cerebellar cortex fear conditioning is accompanied by LTP of the excitatory synapses formed between parallel fibers (PFs) and Purkinje cells (PCs) (5).…”
mentioning
confidence: 99%